The influence of training characteristics on the effect of aerobic exercise training in patients with chronic heart failure: A meta-regression analysis. (1st April 2016) - Vromen, T.; Kraal, J.J.; Kuiper, J.; Spee, R.F.; Peek, N.; Kemps, H.M.
Abstract: Although aerobic exercise training has shown to be an effective treatment for chronic heart failure patients, there has been a debate about the design of training programs and which training characteristics are the strongest determinants of improvement in exercise capacity. Therefore, we performed a meta-regression analysis to determine a ranking of the individual effect of the training characteristics on the improvement in exercise capacity of an aerobic exercise training program in chronic heart failure patients. We focused on four training characteristics; session frequency, session duration, training intensity and program length, and their product; total energy expenditure. A systematic literature search was performed for randomized controlled trials comparing continuous aerobic exercise training with usual care. Seventeen unique articles were included in our analysis. Total energy expenditure appeared the only training characteristic with a significant effect on improvement in exercise capacity. However, the results were strongly dominated by one trial (HF-action trial), accounting for 90% of the total patient population and showing controversial results compared to other studies. A repeated analysis excluding the HF-action trial confirmed that the increase in exercise capacity is primarily determined by total energy expenditure, followed by session frequency, session duration and session intensity. These results suggest that the design of a training program requires high total energy expenditure as a main goal. Increases in training frequency and session duration appear to yield the largest improvement in exercise capacity. Highlights: Exercise training improves exercise capacity in chronic heart failure patients. This effect is mainly determined by total energy expenditure of a program. Energy expenditure is the product of intensity, frequency, duration and length. Increase in frequency and duration elicits the greatest effect on exercise capacity.